Governance from the Grassroots: A Capability-Based Inquiry into Digital Village Financial Management - Andriyus, Andriyus; Elfi Istiqoh, Akhdiva; Juliana, Septa; B. Tenorio, Christine (Journal Public Policy, 2025)
This study investigates the effectiveness of the Village Financial System (VFS) application in Bantan District, Bengkalis Regency, with a focus on how village government capacity influences digital financial management. The research specifically aims to assess the knowledge and skills of village officials, the adequacy of technical and managerial systems, and the role of organizational values and norms in supporting transparent and accountable financial governance. Using a qualitative descriptive approach, the study examines two key units of analysis: village administrations in Bantan District and the Bengkalis Regency Community and Village Empowerment Agency. Data were collected through in-depth interviews, direct observations, and document analysis, and were validated using source, technique, and time triangulation. The findings reveal that although technological infrastructure, such as computer equipment, is generally sufficient, uneven internet access and limited technical skills among village officials lead to frequent data input errors and delayed financial reporting. Strong leadership from village heads and supportive local government regulations help sustain the system, but officials' weak commitment to continuous training constrains optimal implementation. The study concludes that enhanced training, improved internet connectivity, and stronger institutional commitment are critical to achieving transparent, accountable, and effective digital financial management at the village level.